1996
DOI: 10.1111/j.1651-2227.1996.tb14007.x
|View full text |Cite
|
Sign up to set email alerts
|

Xanthogranulomatous pyelonephritis—an unusual renal disease in childhood

Abstract: We report on a 6-year-old boy with Xanthogranulomatous pyelonephritis. This unusual type of renal inflammation has a typical clinical picture that is important to bear in mind. The affected child is often seriously ill with a palpable flank mass leading to initial suspicion of malignancy. Modern imaging procedures help in obtaining a pre-operative diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…It is thought that XGP is a morphological variant of chronic pyelonephritis. This form of pyelonephritis differs from typical chronic pyelonephritis because of the abundant infiltrate of foam cells, which are thought to be macrophage loaded with lipids in XGP 1,9 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is thought that XGP is a morphological variant of chronic pyelonephritis. This form of pyelonephritis differs from typical chronic pyelonephritis because of the abundant infiltrate of foam cells, which are thought to be macrophage loaded with lipids in XGP 1,9 …”
Section: Discussionmentioning
confidence: 99%
“…1 Xanthogranulomatous pyelonephritis should be considered, if there is evidence of local or diffuse destruction of renal parenchyma, poor renal function and clinical features of urinary obstruction or/and urinary infection. 1,8,9 Among physical features, palpable mass is a common finding. The ratio of a palpable mass in a different study was reported as 33 and 66%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation